2016
DOI: 10.1016/j.energy.2016.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the effect of engine settings on the wall heat flux during HCCI combustion

Abstract: Homogeneous charge compression ignition (HCCI) engines are a promising alternative to traditional spark-and compression-ignition engines, due to their potential to achieve a high thermal efficiency and near-zero emissions of NO x and soot. In this work, the heat transfer from the bulk gas to the cylinder wall is measured during motored and HCCI operation in a single cylinder (CFR) engine fueled with n-heptane. Heat flux measurements in the cylinder wall and head show small spatial variation of the heat flux in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…Three other sensor locations are situated in the liner, with the center of the sensor 9 mm below the cylinder head and evenly spaced around the cylinder bore. These probes are Vatell HFM-7 sensors, which consist of a thermopile, capable of determining the heat flux, and a Resistance Temperature Detector or RTD to measure the wall temperature [4]. A Vatell AMP-6 amplifier is used to amplify the electrical output signals, which are directly correlated to the measured quantities through the calibration constants supplied by the manufacturer [4].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three other sensor locations are situated in the liner, with the center of the sensor 9 mm below the cylinder head and evenly spaced around the cylinder bore. These probes are Vatell HFM-7 sensors, which consist of a thermopile, capable of determining the heat flux, and a Resistance Temperature Detector or RTD to measure the wall temperature [4]. A Vatell AMP-6 amplifier is used to amplify the electrical output signals, which are directly correlated to the measured quantities through the calibration constants supplied by the manufacturer [4].…”
Section: Methodsmentioning
confidence: 99%
“…They however all have a general appearance, namely a linear and a logarithmic part, which resembles the momentum wall model given in Equation 2. An example of such a thermal law of the wall is the most simple model, derived by Launder and Spalding [20]: (4) where A + is the van Driest constant which has a value of 26 and T + is the non-dimensional temperature, derived by subtracting the wall temperature T w from the temperature T and dividing by the shear temperature T τ . Together with the relationship between T τ and the wall heat flux q w , this heat flux can be calculated.…”
Section: Equilibrium Wall Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of problems here. First, only recently have experimental data using more advanced measurements techniques become available for the new combustion modes currently being studied [9]. Thus, modeling approaches for these modes have not yet been validated.…”
Section: Introductionmentioning
confidence: 99%
“…A possible solution is the development and use of Thin Film Gauge sensors as described by Thorpe et al [11] and De Cuyper et al [12,13]. Their applicability for engine research has been shown by Broekaert et al [9,14] by measuring the heat flux in a HCCI operated research engine as well as in a production type engine operating in PPC mode [15]. De Cuyper et al [16] also demonstrated their use to measure the heat flux in a production type spark ignition engine.…”
Section: Introductionmentioning
confidence: 99%